2011
DOI: 10.2308/isys-10125
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of IT Investment on Firm Financial Performance

Abstract: We use meta-analysis techniques to examine research choices that affect findings with respect to the return on IT investment. Recent research has established that IT investment is substantially related to firm financial performance. We find, however, that the relationship between IT investment and performance varies, depending on how both financial performance and IT investment are measured. Despite criticism of accounting measures as indicators of IT payoff, we find that the relationship is often stronger in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 64 publications
3
30
0
3
Order By: Relevance
“…This result supports much of previous research, such as [2] [17] [18] [3]. This study indicates different levels of firm performance for the same amount of IT spending over varying levels of good CG.…”
Section: A Corporate Governance and It Expendituresupporting
confidence: 90%
See 2 more Smart Citations
“…This result supports much of previous research, such as [2] [17] [18] [3]. This study indicates different levels of firm performance for the same amount of IT spending over varying levels of good CG.…”
Section: A Corporate Governance and It Expendituresupporting
confidence: 90%
“…Besides these promising influences of IT adoption on the organization, further research indicated that discrepancies of the impact, especially on financial performance, exist [3]. Even, a broader investigation which studied the relationships between IT and organizational performance revealed contradictory evidence [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a COS setting, members can leverage the collaborative rent to improve their part of the combined value chains' business processes, which means that any leverage of collaborative rent will first affect the business processes of the COS's members. This situation is consistent with the notion that the first focal point of measuring IT's business value should be the IT-managed business processes (Alter, 2003;Dehning & Richardson, 2002;Lim, Dehning, Richardson, & Smith, 2011). Members' improved business processes assists in their leveraging their assets and investments and in lowering their cost of sales and service operations.…”
Section: Collaborative Rent-generating Potential and Business Value Osupporting
confidence: 67%
“…In this study, the researcher uses both firm level and more aggregated level studies (industry and national), which is not done by Kohli and Devaraj (2003) nor by this paper. Since we discussed IT payoff and meta-analysis research, we would like to mention also a related study done by Lim, Dehning, Richardson, and Smith (2011). The focus of the authors is the effect of IT on firms' financial performance.…”
Section: Productivity Paradoxmentioning
confidence: 99%